Radiobiological evaluation of prostate cancer IMRT and conformal-RT plans using different treatment protocols. (August 2017) - Mavroidis, Panayiotis; Komisopoulos, Georgios; Buckey, Courtney; Mavroeidi, Margarita; Swanson, Gregory P.; Baltas, Dimos; Papanikolaou, Nikos; Stathakis, Sotirios
Highlights: IMRT plans optimized with the RTOG0415 criteria showed similar results with CRT. General constraints are not suitable for optimally sparing the rectum using IMRT. Treatment plans with higher quality (lower NTCP for the same TCP) showed higher risk for secondary cancer. Treatment plan optimization should be complemented with the risks for secondary cancer. Abstract: The purpose of this study is to evaluate the clinical efficacy of both step-and-shoot IMRT and 3D-Conformal Radiation Therapy modalities (CRT) in treating prostate cancer using radiobiological measures. Another aim was to estimate the risks for developing secondary malignancies in bladder and rectum due to radiotherapy from the corresponding modalities. The treatment plans of ten prostate cancer patients were developed using IMRT and CRT. For the IMRT plans, two beam energies and two treatment protocols were used (the RTOG 0415 and a most restrictive one proposed by Fox Chase Cancer Center (FCCC)). For the evaluation of these plans, the complication-free tumor control probability, the total probability of injury, the total probability of control/benefit, and the biologically effective uniform dose were employed. Furthermore, based on the dosimetric data of IMRT and CRT, the risk for secondary malignancies was calculated for bladder and rectum. The average risk for secondary malignancy was lower for the bladder (0.37%) compared to the rectum (0.81%) based on all the treatment plans of the ten prostate cancer patients. The highest average risk for secondary malignancy for bladder and rectum was for the CRT-6X modality (0.46% and 1.12%, respectively) and the lowest was for the IMRT RTOG-18X modality (0.33% and 0.56%, respectively). The ≥ Grade 2 LENT/SOMA response probability was lower for the bladder than for the rectum in all the plans. For the bladder the highest average value was for the IMRT RTOG-18X (0.9%) and the lowest was for the CRT-18X modality (0.1%). For the rectum, the highest average value was for the IMRT RTOG-6X (11.9%) and the lowest was for the IMRT FCCC-18X modality (2.2%). By using radiobiological measures it is shown that the IMRT FCCC plans had the lowest risks for normal tissue complications, whereas the IMRT RTOG had the highest. Regarding the risk for secondary malignancies, the CRT plans showed the highest values for both bladder and rectum.